PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 2 GAYAU SAKTI TAHUN PELAJARAN 2014/2015 - Soleha, Soleha (UNIVERSITAS MUHAMMADIYAH METRO, 2016)
The aims of this research were to increase the student learning outcomes by implementation of cooperative learning model of Make A Match. The method of the research was Classroom Action Reserach. The data collected by the observation sheet, formatif test sheet (test student learning outcomes). The results of the study implementation of cooperative learning model of Make A Match proven to improve learning performance followed by increased the student learning outcomes, enthusiastic students to participate in learning. The result showed that Â Percentage student learning outcomes 41.6 % in the first cycle to 93.3 % in the second cycle .Keywords: student learning outcomes, cooperative learning model of Make A Match